2005
DOI: 10.1373/clinchem.2004.046557
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-B-Type Natriuretic Peptide Concentrations Are Markedly Higher in the Umbilical Cord Blood of Newborns than in Their Mothers

Abstract: The mechanism behind the pronounced effect of estrogen on CRP is most likely an effect on gene expression in the liver. Strong support for this assumption that this effect is mediated by estrogen itself and not by a factor stimulated by estrogen comes from the observations that the effect is dose-dependent, is seen in both women and men, and occurs only after oral treatment. It is not clear whether the effect of estrogen on gene expression is mediated by transcriptional activation or RNA stabilization. No horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
27
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 7 publications
12
27
0
2
Order By: Relevance
“…cTnT and NTpBNP were unaffected by gestation, birth weight, sex, chorioamnionitis and mode of delivery. This is consistent with the results of other groups [17][18][19][20] and suggests that assays of cTnT and Abbreviations: cTnT, cardiac troponin T; FS, shortening fraction; LA:Ao ratio, left atrial to aortic root ratio; Min-Max, minimum to maximum value; mVcfs, mean circumferential fiber shortening velocity; NTpBNP, N-terminal-pro-B type natriuretic peptide; PDA, patent ductus arteriosus. …”
Section: Discussionsupporting
confidence: 90%
“…cTnT and NTpBNP were unaffected by gestation, birth weight, sex, chorioamnionitis and mode of delivery. This is consistent with the results of other groups [17][18][19][20] and suggests that assays of cTnT and Abbreviations: cTnT, cardiac troponin T; FS, shortening fraction; LA:Ao ratio, left atrial to aortic root ratio; Min-Max, minimum to maximum value; mVcfs, mean circumferential fiber shortening velocity; NTpBNP, N-terminal-pro-B type natriuretic peptide; PDA, patent ductus arteriosus. …”
Section: Discussionsupporting
confidence: 90%
“…Reasons for this are unknown but resemble the increased CK-MBs and troponins also found in neonates although the 97.5th percentiles for these latter cardiac markers decrease more rapidly to values found in older children by around 6 months of age. This data is supported by the work of Hammerer-Lercher et al and Bakker et al [8,9] who showed NT-proBNP to be significantly higher in plasma from cord blood than in maternal plasma. N values in previous studies have been far too small to reliably define reference intervals for males and females at each age group [8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 71%
“…This data is supported by the work of Hammerer-Lercher et al and Bakker et al [8,9] who showed NT-proBNP to be significantly higher in plasma from cord blood than in maternal plasma. N values in previous studies have been far too small to reliably define reference intervals for males and females at each age group [8][9][10][11][12][13]. Our data differs from that reported by Rauh et al [13] and Koch et al [26].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Such high value observed among healthy NBIs in the first days of life tends to return to normal with physiological loss in weight reaching a level similar to that observed in adults. [5][6][7] In the neonatal population, BNP measurements vary widely. Several studies have reported BNP levels ranging from 200 to 6000 pg/mL.…”
Section: Introductionmentioning
confidence: 99%